Theliberalisation process of the German electricity market: Strategies and opportunities - Claudia Kemfert (Fondazione Eni Enrico Mattei (FEEM), 1999)
Within this paper an oligopolistic German electricity market is modelled by a game theoretic modelling tool representing a Nash equilibrium. Due to European electricity market liberalisation electricity producing and trading firms react strategically like global market players by joining and merging market shares and gains. On the way to perfect competition within the electricity market strategic behaviour like co-operation or refusal of collaboration or net access will determine the development of a market and energy suppliers structure. Presently, the German electricity market is determined by strategic behaviour of energy firms so that a full competitive market has not been reached yet. An oligopolistic market structure emerged and is characterised by a mutual influence of prices due to market shares and power. Computationally, this can be modelled by a Nash equilibrium path based on game theoretic modelling approaches. Within the Nash equilibrium, electricity firms react strategically by optimising their profits with an opportunity to enlarge their market shares influencing prices and demand. A Nash equilibrium is reached by an optimal solution of strategic actions considering strategic behaviour by all other market actors. A non Nash equilibrium or full competition case equals prices and marginal costs in order to determine and optimise profits of firms. The computational game theoretic modelling tool has been developed by the programming language GAMS written as a mixed complementary problem (MCP) solved by the GAMS algorithm MILES resolving non linear complementary problems based on a generalised Newton method iteratively. It turns out that the Nash equilibrium solution fulfils the optimal criteria of mathematical solution whereas the full competition scenario leads to implausible high market shares resulting though in an oligopolistic market structure characterised by a Nash equilibrium. Within the Nash equilibrium mutual profit maximisation and strategic behaviour lead to regional market shares by firm mergers and establish regional price variations resulting in distinctive net trades.
Keywords: C7; D2; Q4; R3; 330; Game theoretic modelling; electricity market liberalisation; Elektrizitätswirtschaft; Energiemarkt; Deregulierung; Oligopol; Marktanteil; Spieltheorie; Theorie; Deutschland